Environmental Benefits of Turbo Roundabout: A Case Study of Noise and Air Pollution Modelling in the Village of Košťany Nad Turcom, Slovakia - Jandacka Dusan; Cingel Andrej; Brna Matej; Cingel Michal (Civil and Environmental Engineering)
Road transport represents a significant source of environmental pollution by air pollutants and noise. An important task is therefore to find ways to reduce these negative impacts. One option is also to change the conditions of the road transport infrastructure, for example by re-arranging the spatial layout of intersections and thus changing the driving mode of vehicles. The task of this study is to analyze the impact of the potential reconstruction of the intersection on the noise and air pollution load in its surroundings using modelling with the CadnaA program. This is a proposal to change the intersection (PK) to a turbo roundabout (TOK), with a specific structural layout and driving mode. As part of the study, a traffic survey was carried out to obtain detailed information about the volume and directions of road traffic at the intersection. The traffic volume at the intersection is specific to a high proportion of trucks, which also significantly affected the (un)change in the environmental load by noise and emissions. From the modeled variants, a reduction in noise pollution was observed, but no significant positive change in air pollution was demonstrated at TOK. At the observation point MP1, an increase in noise by 2 dB was recorded, and at MP4 a decrease of 3.6 dB. PM10 concentrations did not decrease at any observation point and increased most at MP1 by 7 µg/m3 according to the model.